Pengembangan Buku Suplemen Biologi Materi Keanekaragaman Hayati Bersumber Keunggulan Lokal Daerah Pesisir - Ningrum, Tika Aryanti; Tinneke L, Sonja Verra; Boleng, Didimus Tanah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This study aims to develop a biology supplement book and find out the quality of a biology supplement book on biodiversity material sourced from local excellence in coastal areas, which is developed as a suitable source of learning biology for grade X students of SMA / MA. This research includes Research & Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The product assessment was conducted by 2 validators, 4 Biology Teachers, and 103 students. The instrument used was a questionnaire sheet. The assessment of student response trials was conducted at SMA Negeri 1 Muara Badak and SMA Negeri 2 Muara Badak. The data analysis technique uses descriptive qualitative and quantitative. Based on the results of the overall assessment, an average percentage of questionnaires per assessment indicator was obtained, namely material coverage indicators 89.9%, presentation indicators 90.4%, linguistic indicators 87.8%, graphic design indicators 89.3%, included in the Very Eligible (SL) category. The assessment obtained from the experts produced a percentage of eligibility of 91.25% including the Very Eligible (SL) category; biology teacher 90% eligibility percentage. Thus, biology supplement books on biodiversity materials sourced from local excellence in coastal areas are of good quality and are very suitable to be used as learning resources for class X students of SMA / MA. Obstacles encountered during the research and development of biology supplement books, including the preparation of materials, manufacturing of products and barriers in the testing class.